YOUTH INITIATIVES IN TOURISM IN THE ERA OF DIGITALIZATION AND PANDEMIC - N. A. Zamyatina; A. V. Zbarskaya (Вестник университета)
The rapid digitalization of the economy since the early 2010s thanks to the rapid development of the mobile Internet and artificial intelligence was accelerated by the COVID-19 coronavirus pandemic, which caused catastrophic losses in international tourism in 2020. This article considers the perception of the tourist region by the young generation of the era of smartphones and social networks and sets objectives of adapting tourism in the world of VUCA – a world of instability, uncertainty, complexity and ambiguity. The priority strategies of tourism development in the regions: the introduction of the unseen tourism management technologies and creation of the online platform of youth leisure, development of concepts modern use of historic buildings while preserving their historical authenticity and romantic atmosphere, organization of public spaces for the exchange of experiences between generations on the basis of mutuall interest and encouragement of projects engaging young people with disabilities. There is a need for long-term planning and the formation of a global system of universal values and human understanding of their place in the “new reality”. This vector of development will lead to a new level of humanity in the future 5–10 years.